Church and Society in the Past Century (1918–2018) - LUKÁCS, Olga (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2020)
The Department of Reformed Theology and Music of Babeș–Bolyai University in Kolozsvár/Cluj-Napoca in joint venture with the Károli Gáspár University of the Reformed Church in Hungary headquartered in Budapest and the Reformed Public and Cultural Centre Foundation [Református Közéleti és Kulturális Központ Alapítvány] held a conference featuring the title above in Kolozsvár/Cluj-Napoca on 7–8 June 2018. The volume contains the written material of the joint conference in English.